Study of the Significance of Abnormal Returns Earned by Investing Based on Analysis Recommendations: Examining the Impact of Brokerage Analyst Recommendations on Abnormal Returns in the Indian Stock Market (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The usefulness of brokerage analyst recommendations in the Indian stock market. Usefulness of recommendations has been assessed in terms of informative value, that is, informational contribution to the stock market, as well as predictive value, that is, enabling investors to earn abnormal returns on their stock investments. Further, we investigated two key determinants of usefulness, information uncertainty and analyst behaviour. The first determines the opportunity as well as the challenge faced by equity analysts, while the second impacts the quality of their research. The research is based on empirical research of brokerage analyst recommendations in India using a large representative sample of individual broker recommendations as well as average recommendations of a cross-section of 200 firms over a period of six years (April 2009 to March 2015). Informational contribution was measured by estimating abnormal returns around the release of the recommendation, while the ability to predict investment returns was analysed over a long investment horizon using the event study methodology. The study concludes that analyst recommendations, in aggregate, are useful since they enhance information availability in the market, as well as enable investors to earn abnormal returns, provided that specific trading strategies are employed to use such recommendations.